The Implementation Of Daily Journal To Improve Writing Skills For University Students - Salsabila, Khansa; Mika, Marliana; Deandra Salvita, Viga; Hermawan, Muhammad Rivaldy; Husna HR, Nida (Universitas Cokroaminoto Palopo, 2024)
This study focused on implementing Daily Journal as a student’s writing activity. The study's objective is to impact the implementation of a daily journal on students' writing skills. The research method used in this study is quantitave. The subject of the study was 32 students majoring in English Education in one of Islamic University in Indonesia. Participants will take a pre and post-test and from there the researcher can compare their vocabulary and grammar skills in written form. The results of both tests will be subjected to a two-sample paired t-test analysis conducted using the Statistical Package for the Social Sciences (SPSS) software program. The test resulted in a significance value of 5%, providing sufficient evidence for a statistical change in post-treatment testing. The results of this study indicate that Daily Journal is an effective tool in enhancing English writing skills among the students in university level.